Fenomena Biro Jodoh melalui Aplikasi Tantan Era Milenial dalam Pandangan Hadis - Muhajirin Muhajirin; Putri Regina Patricia (Jurnal Riset Agama, 2022)
This study aims to discuss the phenomenon of matchmaking bureaus through the millennial era tantan application in the view of hadith. The methods used by researchers are descriptive-qualitative through literature studies. The results and discussions in this study include the definition of a matchmaking bureau, the positive and negative impacts of a matchmaking bureau, the definition of a tantan application, the mechanism for using a tantan application and hadith analysis. This study concluded that based on the hadith of Ibn Majah gained an understanding that it is okay to make friends and even find a partner through social media. However, you must be more careful because in addition to many positive impacts, of course there are negative impacts that can occur if misused.